2004
DOI: 10.3168/jds.s0022-0302(04)73518-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Lactation Curve in Dairy Cattle on Farms in Central Mexico

Abstract: Accurate knowledge of lactation curves has an important relevance to management and research of dairy production systems. A number of equations have been proposed to describe the lactation curve, the most widely applied being the gamma equation. The objective of this work was to compare and evaluate candidate functions for their predictive ability in describing lactation curves from central Mexican dairy cows reared under 2 contrasting management systems. Five equations were considered: Gaines (exponential dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
4
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 17 publications
14
57
4
6
Order By: Relevance
“…The model by Dijkstra et al (1993) showed higher estimates of the peak day than those of the other models, in all the subgroups. A similar result was reported by Val-Arreola et al (2004). Therefore, it is possible that the model by Dijkstra et al (1993) is more suitable to represent lactations whose peak day occurs on a day farther from the beginning of lactation (Figure 3).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The model by Dijkstra et al (1993) showed higher estimates of the peak day than those of the other models, in all the subgroups. A similar result was reported by Val-Arreola et al (2004). Therefore, it is possible that the model by Dijkstra et al (1993) is more suitable to represent lactations whose peak day occurs on a day farther from the beginning of lactation (Figure 3).…”
Section: Resultssupporting
confidence: 65%
“…In absolute values the model by Dijkstra et al (1993) showed a better adjustment than the others in all the goodness of fit measurements. Val-Arreola et al (2004) also observed the better adjustment of the model by Dijkstra et al (1993) over the models by Brody et al (1923), Wood (1967), Rook et al (1993) and by Pollott (2000) for lactations of animals on more technological farms. The model by Dijkstra et al (1993) showed a higher percentage of convergence in the high production subgroups than the low and medium production subgroups.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Similarly, the energy requirements for milk production reflect the shape of the lactation curve. The lactation curve of the dairy cow was represented using the equation of Dijkstra et al (1997) which was found to be the most appropriate equation for cows reared under small-scale systems in central Mexico (Val-Arreola et al, 2004a).…”
Section: Milk Production and Energy Requirementsmentioning
confidence: 99%
“…Previous comparisons of production curves indicated that the Dijkstra curve provided the most accurate estimates of peak milk yield and time of peak milk yield and that smaller models are preferable (Dematawewa, et al, 2007, Val-Arreola, et al, 2004. The Dijkstra curve was chosen as the production curve to model milk yield, based on the BIC in the current study and previous findings.…”
Section: Fitting Lactation Curvesmentioning
confidence: 99%